In vitro Development of Resistance to Azithromycin in Pseudomonas aeruginosa (Bangladesh Pharmaceutical Journal, 2018)
Antimicrobial resistance has been considered as a growing public health problem all over the world. Due to improper use of antibiotics many bacterial species including the Pseudomonas aeruginosa become resistant. So, the objectives of this study were to determine the success or failure of antibiotic therapy. Tests were performed in vitro and measured the growth response of an isolated bacterium to a particular drug. This study determined the zone of inhibition, minimum inhibitory concentration (MIC) and time at which bacteria showed resistance. From sensitivity test, it showed that P. aeruginosa is sensitive to azithromycin antibiotic. MIC level of P. aeruginosa that was found from the analysis was 3 μg/ml and from further analysis it was found that P. aeruginosa grew resistance when it got up to 2.5 μg/ml concentration of antibiotic below MIC level for 24 hours. When the P. aeruginosa was treated with the concentration upto 2.5 μg/ml for 24 hours then it showed growth at the concentration of MIC level. It means that P. aeruginosa got the drug below MIC level for a certain period and became resistant to azithromycin.Bangladesh Pharmaceutical Journal 21(1): 42-46, 2018